Endovascular and Percutaneous Treatment of Pediatric Portosystemic Varices: A Case Review - Dabrowiecki, Alexander; Monroe, Eric J.; Romero, Rene; Gill, Anne E.; Hawkins, C. Matthew (Digestive Disease Interventions, 2019)
Portal hypertension is a significant cause of morbidity and mortality in pediatric patients. Complications of portal hypertension include development of portosystemic varices. The most common type of portosystemic varices are gastroesophageal varices; however, other ectopic varices can also be a cause of recurrent, life-threatening gastrointestinal bleeding. Problematic ectopic varices include isolated gastric, anorectal, small bowel, roux-limb, and stomal varices. There are no standardized treatment guidelines on how to manage ectopic varices in children; however, new innovations in endovascular treatment options provide potential therapeutic alternatives when varices are refractory to conventional therapy. This review provides a case-based literature review for endovascular treatment of isolated gastric, anorectal, small bowel, roux-limb, and stomal ectopic varices in children (age 0-9 years) and adolescents (age 10-19 years).
Keywords: portosystemic varices; ectopic varices; venous intervention; pediatric interventions